2016
DOI: 10.1902/jop.2015.150353
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Lipid Peroxidation in Patients With Generalized Chronic Periodontitis and Acute Coronary Syndrome

Abstract: To our knowledge, this study is the first to investigate salivary MDA levels in patients with ACS and their correlations with serum hsCRP and plasma fibrinogen levels. The results indicate that salivary MDA levels could be a biomarker for cardiovascular and/or periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 46 publications
2
22
0
4
Order By: Relevance
“…Studies have reported that lipid peroxide produced by periodontal inflammation, such as observed in our animal model through gingival and renal MDA levels, diffuses into the bloodstream (Nguyen, Ngo, Promsudthi, & Surarit, 2016;Sobaniec & Sobaniec-Lotowska, 2000) causing systemic damages in several organs, such as heart, liver, brain and kidneys, as observed by Tomofuji et al (2011). Our data corroborate these findings for renal tissues.…”
Section: Groupssupporting
confidence: 89%
“…Studies have reported that lipid peroxide produced by periodontal inflammation, such as observed in our animal model through gingival and renal MDA levels, diffuses into the bloodstream (Nguyen, Ngo, Promsudthi, & Surarit, 2016;Sobaniec & Sobaniec-Lotowska, 2000) causing systemic damages in several organs, such as heart, liver, brain and kidneys, as observed by Tomofuji et al (2011). Our data corroborate these findings for renal tissues.…”
Section: Groupssupporting
confidence: 89%
“…Some analytical methods have been developed to study salivary oxidative stress biomarkers (glutathione peroxidase, catalase, protein carbonyls, 8-hydroxy-2'-deoxyguanosine), but few of them determined lipid peroxidation compounds, such as malondialdehyde (MDA) [14][15][16], and prostanoids (e.g. 15-F 2t -IsoP) [10].…”
Section: Introductionmentioning
confidence: 99%
“…[31] It should be noted that the MDA content increases in case of lung cancer, but we found no statistically significant increase in this indicator even despite the numerous confirmations of this fact in the literature. [22][23][24][25][26][27][28][29][30] During the performed studies, we have elicited the fact of an increase in the level of MM, which is an indirect evidence of excessive generation of active oxygen metabolites: Superoxide radicals and hydrogen peroxide. [36] Hydroxyl radicals are capable to damage the phosphoglyceride membrane structures of cell membranes and its organelles.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] There is a number of scientific works [21][22][23] dedicated to the study of indicators of endogenous intoxication and lipid peroxidation in saliva; however, the overwhelming majority of studies are limited to an evaluation of the MDA content. [22,24,25] The changes in the lipid peroxidation processes in the saliva of patients with oral cavity precancer and cancer are described by the example of MDA. [26,27] Yet, despite the numerous literature data that show an increase in the level of MDA in saliva in case of malignant tumors, [28,29] we have noted that the character of MDA concentration change in case of lung cancer is nonlinearly connected with the tumor progression.…”
Section: Introductionmentioning
confidence: 99%